5. STRATEGI MENGEFEKTIFKAN GAPOKTAN SEBAGAI LEMBAGA EKONOMI DIPERDESAAN - Abdullah Usman (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2009)
ABSTRACT Farmers group union (Gapoktan) can bee perceived as a breaktrough to enhance farmer’s bargaining position in market both output market, input market and money market. This isyu is getting relevant especially in liberalisation era. Such institution is extremly important to shield farmers dan informal sectors from modern sector’s invation. Farmer’s weak position in global competition can be the cause of why modern retail like Alfamart which has been partly owned by Carrefour dominates the outlet of agribussness products. This paper attempt to highlight some thoughs related to strategy to emprove the union to be more effective. This descriptive study uses qualitatif data and information, presented to encourage scientific discussion. After doing overviewing union concept, this paper attempts to raise theoretical fondation to evaluate the union. By then, it can be evaluate the position of current union, understanding the problems and their solutions. The union can be studied using public good theory, market structure, market separation dan price discrimination, market information, producer behavour. To enhance efectiveness of the union can use the strategi concern to bottom up initial establishing, and by maintaining condusive bussiness climate. ABSTRAK Gabungan kelompok tani (Gapoktan) bisa dipandang sebagai terobosan usaha untuk memperkuat posisi rebut tawar (bargaining position) petani dipasar. Isyu ini semakin relefan dikaji terutama dalam konteks liberalisasi perdagangan dan membentengi usaha lokal dalam persaingan global dengan menggunakan kelembagaan modern seperti ritel alfamart yang sekarang sebagian sahamnya sudah diacquisisi oleh Carrefour, yang membuat pengusaha lokal semakin terpinggirkan. Paper ini berupaya menelaah beberapa kemungkinan strategi didalam mengefektifkan gapoktan yang selama ini masih belum terasa peranannya. Kajian ini bersifat diskriptif dengan menggunakan data dan informasi qualitatif yang dikemas dalam format diskusi ilmiah. Paper ini menyoroti (overview) gapoktan dan mencari landasan teoritisnya sebagai acuan dalam pengkajian. Empirik dilapangan dievaluasi dengan teoritis sehingga bisa dipahami posisi pelaksanaan gapoktan, masalah dan solusinya. Gapoktan dapat dikaji dengan menggunakan teori public good, struktur pasar, market separation dan price discrimination, informasi pasar, dan prilaku produsen. Untuk meningkatkan efektiifitas gapoktan bisa digunakan strategi pembentukan yang bottom up dan strategi membangun iklim usaha yang kondusif.